Kazakh Variants of the Epic Korugly - Pakizat Auyesbayeva, Togzhan Akimova, Tokhtar Albekov, Karashash Alpysbayeva, Zhumashay Rakysh, (Opción, 2019)
In the article, the questions of the appearance of the epicKorugly on Kazakh territory are investigated. The methodologicalbasis includes theoretical works of national and foreign researchers inthe field of Korogly studies and epic studies. As a result, the maincharacter of the epic Korugly is born in a miraculous way. Most of theepic works develop into a voluminous story, being complemented by apoetic form, and represent a whole work. In conclusion, more than tenepic variants have been revealed and about twenty variants as theirconclusion that do not duplicate each other